Alternatif Kebijakan Public Service Reform dalam Meningkatkan Kualitas Pelayanan Publik - Joni Dawud (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
The improvement of public service quality has turned out to be the main objectives in the public sector reform. The policy target is to promote the non-government sectors, namely, the private sector and society to increase its participation inÂ providing public service. In addition, the internal policy needs to be reformulated, concerning both the system and the personnel implementing the system.Â